FRI0316 The Efficacy and Safety of Subcutaneous Tocilizumab versus Intravenous Tocilizumab in Combination with Traditional DMARDS in Patients with RA at Week 97 (SUMMACTA). (10th June 2014) - Burmester, G.; Rubbert-Roth, A.; Cantagrel, A.; Hall, S.; Leszczynski, P.; Feldman, D.; Rangaraj, M.J.; Roane, G.; Ludivico, C.; Mysler, E.; Bennett, M.J.; Rowell, L.; et al.
Abstract : Background: Tocilizumab (TCZ) is approved as an intravenous (IV) formulation globally and subcutaneous (SC) formulation in the US for the treatment of adult rheumatoid arthritis (RA). In the SUMMACTA study, efficacy and safety of TCZ-SC weekly (qw) was demonstrated through week (wk) 24 in patients (pts) with RA with an inadequate response to disease-modifying antirheumatic drugs (DMARDs). 1 TCZ-SC also demonstrated sustained efficacy through wk 49. 2 Objectives: To evaluate the efficacy and safety of TCZ-SC vs TCZ-IV, including in pts who switched from TCZ-IV to TCZ-SC and vice versa, through wk 97. Methods: SUMMACTA is a 2-year, randomized, active-controlled, parallel-group phase 3 study comprised of a 24-wk double-blind period, followed by re-randomization for a 72-wk open-label extension period. Pts (n=1262) were randomized 1:1 to receive TCZ-SC 162 mg qw (n=631) or TCZ-IV 8 mg/kg every 4 wks (q4w; n=631) in combination with traditional DMARDs. After 24 wks, pts who initially received TCZ-SC were rerandomized 11:1 to TCZ-SC qw (n=521) or TCZ-IV q4w (n=48) and pts who initially received TCZ-IV were rerandomized 2:1 to TCZ-IV q4w (n=372) or TCZ-SC qw (n=186). Results: A total of 76 (14.6%), 61 (16.4%), 8 (16.7%), and 26 (14.0%) patients from the TCZ-SC, TCZ-IV, TCZ-SC to TCZ-IV, and TCZ-IV to TCZ-SC groups, respectively, withdrew from the study through wk 97. The percentages of pts who achieved ACR20/50/70 responses, DAS28 remission, and an improvement from baseline in HAQ-DI ≥0.3 were sustained through wk 97 (Table) and comparable across all treatment groups. The safety profiles of switchers were similar to that of pts with continuous TCZ-SC or TCZ-IV treatment (Table) and consistent with the well-established safety profile of TCZ-IV. No anaphylaxis cases were identified. The proportions of pts who developed anti-TCZ antibodies remained low and were comparable across treatment groups through wk 97, and no association between anti-TCZ antibody development and clinical response or AEs was observed. Conclusions: These data demonstrate that long-term efficacy and safety of TCZ-SC qw is maintained and remains comparable to TCZ-IV, with the exception of injection site reactions, which were more commonly seen with TCZ-SC but comparable to other SC RA treatments. The efficacy and safety profiles of pts who switched were comparable to those in pts who remained on TCZ-IV or TCZ-SC. Thus, TCZ-SC could provide a more convenient administration option and an opportunity of home injection in pts with RA. References: Burmester GR, et al. Ann Rheum Dis. 2014;73(1):69-74. Burmester GR, et al. Arthritis Rheum. 2013;65(suppl 10) [abstract 464]. Disclosure of Interest: G. Burmester Grant/research support: Roche, Abbott, Pfizer, UCB, BMS, MSD, Consultant for: Roche, Chugai, Pfizer, UCB, BMS, Speakers bureau: Roche, Pfizer, MSD, BMS, Abbott, A. Rubbert-Roth Grant/research support: Roche, Pfizer, Consultant for: Roche, Chugai, Pfizer, MSD, Abbott, UCB, Speakers bureau: Roche, UCB, A. Cantagrel Grant/research support: UCB, Pfizer, Consultant for: BMS, Chugai, Roche, UCB, Abbott, Pfizer, S. Hall: None declared, P. Leszczynski Consultant for: Roche, D. Feldman: None declared, M. Rangaraj Grant/research support: Roche, G. Roane: None declared, C. Ludivico Grant/research support: Roche, BMS, Pfizer, Human Genome Science, Lilly, Sanofi-Aventis, Speakers bureau: BMS, E. Mysler Grant/research support: Roche, Consultant for: Roche, Speakers bureau: Roche, M. Bennett Employee of: Roche, L. Rowell Employee of: Roche, M. Bao Employee of: Genentech, Inc. DOI: 10.1136/annrheumdis-2014-eular.1347